Peran Customer Satisfaction dalam Memediasi Pengaruh Service Quality terhadap Repurchase Intention di Pandan View Mandeh Resto (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of service quality on repurchase intention with customer satisfaction as a mediating variable at Pandan View Mandeh Resto. The study was conducted with a quantitative approach and used a causal associative design to explain the relationship between variables. The population in this study were all customers who had received services and consumed food and drinks at Pandan View Mandeh Resto within the past year, with a minimum age requirement of 17 years. The sample set was 130 respondents and was obtained through questionnaire distribution. Data collection was carried out using a questionnaire instrument that had been prepared based on indicators from the research variables. Furthermore, the data obtained were analyzed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method with the help of the Smart-PLS application. The analysis carried out included outer model testing (validity and reliability), inner model testing (relationships between latent variables), hypothesis testing, and mediation testing. The results showed that service quality has a positive and significant influence on customer satisfaction. Furthermore, customer satisfaction has been shown to have a positive and significant effect on repurchase intention. Furthermore, service quality also has a significant positive effect on repurchase intention. Mediation analysis shows that customer satisfaction acts as a partial mediator in the relationship between service quality and repurchase intention. This means that some of the influence of service quality on repurchase intention occurs through customer satisfaction, while others occur directly. These findings emphasize the importance of maintaining and improving service quality to create satisfaction, which in turn impacts customer loyalty.